The Experience of Legal Supervision of Hungarian Local Governments in the Light of Debt Settlement Procedures - Árva, Zsuzsanna (Public Governance, Administration and Finances Law Review, 2025)
The study focuses on the financial segment of the legal supervision of local governments in Hungary. It examines the experience of legality supervision, with a special focus on professional assistance and financial instruments, based on the reports of government offices. Drawing on the academic literature, it examines the general means of supervision, the main international approaches to financial supervision and the experience of Hungarian financial control. In the latter context, it relies on the analyses and reports of the State Audit Office of Hungary and takes stock of the debt resolution procedures that have occurred in Hungary after 2014, which the paper hypothesises may, in some cases, point to the limits of the means of legal supervision in the financial field. The study assesses recent legislative proposals and notes the importance of preventive instruments. It further points out that the most severe instruments often have a preventive effect.